The effect of relationship marketing tactics on customer loyalty within the Malaysian mobile telecommunication industry: the mediating role of relationship quality / Mohamad Fariz Abdullah - Abdullah, Mohamad Fariz (2017)
The subject area of this study is concerned with the effect of relationship marketing tactics and relationship quality on customer loyalty in a competitive mobile service industry in Malaysia. Relationship marketing nowadays is an important topic, especially to the businesses that involve a service because it can offer to the establishment of long-term and stable relationship between service providers and the customer , thereby encouraging customer loyalty (Rizan et aI., 2014). This study has explored the applicability of the Pull-Push-Mooring (PPM) Migration Model by Bansal et.al, (2005) and measurement of the relationship of The Commitment-Trust Relationship Marketing Theory by Morgan & Hunt (1994). This study also focused on the main players of mobile telecommunication service providers in Malaysia , which are Maxis, Celcom, DiGi, and others. A total of 382 mobile phone users from four major cities in Malaysia completed a questionnaire to provide the empirical data for the analysis. A quantitative research method was applied to test the hypotheses developed in this study using SPSS version 20. Multiple regressions analysis and bootstrapping method by Preacher and Hayes (2008) were employed in order to test the hypothesized path model. The findings provided significant insights into both theoretical and managerial implications ; contributed to relationship marketing literature by providing empirical evidence that relationship marketing tactics have an effects on the customer loyalty. Emotion as a mooring factor in the relationship marketing tactics was found to be significantly influenced the customer loyalty . The mediating effects of relationship quality also supported the Morgan & Hunt (1994)' s theory , which stressed the importance of its dimension ; commitment and trust as a key in developing a successful marketing relationship.